Cholinergic mechanisms in spinal locomotion—potential target for rehabilitation approaches - Jordan, Larry M.; McVagh, J. R.; Noga, B. R.; Cabaj, A. M.; Majczyński, H.; Sławińska, Urszula; Provencher, J.; Leblond, H.; Rossignol, Serge (Frontiers in Neural Circuits, 2014)
Previous experiments implicate cholinergic brainstem and spinal systems in the control of locomotion. Our results demonstrate that the endogenous cholinergic propriospinal system, acting via M2 and M3 muscarinic receptors, is capable of consistently producing well-coordinated locomotor activity in the in vitro neonatal preparation, placing it in a position to contribute to normal locomotion and to provide a basis for recovery of locomotor capability in the absence of descending pathways. Tests of these suggestions, however, reveal that the spinal cholinergic system plays little if any role in the induction of locomotion, because MLR-evoked locomotion in decerebrate cats is not prevented by cholinergic antagonists. Furthermore, it is not required for the development of stepping movements after spinal cord injury, because cholinergic agonists do not facilitate the appearance of locomotion after spinal cord injury, unlike the dramatic locomotion-promoting effects of clonidine, a noradrenergic α-2 agonist. Furthermore, cholinergic antagonists actually improve locomotor activity after spinal cord injury, suggesting that plastic changes in the spinal cholinergic system interfere with locomotion rather than facilitating it. Changes that have been observed in the cholinergic innervation of motoneurons after spinal cord injury do not decrease motoneuron excitability, as expected. Instead, the development of a “hyper-cholinergic” state after spinal cord injury appears to enhance motoneuron output and suppress locomotion. A cholinergic suppression of afferent input from the limb after spinal cord injury is also evident from our data, and this may contribute to the ability of cholinergic antagonists to improve locomotion. Not only is a role for the spinal cholinergic system in suppressing locomotion after SCI suggested by our results, but an obligatory contribution of a brainstem cholinergic relay to reticulospinal locomotor command systems is not confirmed by our experiments.